1987
DOI: 10.1515/znc-1987-7-812
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Metabolic Model of Acifluorfen Activity

Abstract: A ciflu orfen. Diphenyl Ether, Bleaching H erbicides, CarotenoidsThe p a ra -nitro substituted diphenyl ether herbicides which cause rapid plant pigment photobleaching can be divided into two categories: 1. those that have a photosynthetic requirem ent for activity (e.g. oxyfluorfen) and 2. those that have no apparent m etabolic requirem ent for activity (e.g. acifluorfen). A m odel is presented for the latter category, in which the diphenyl ether herbicide interacts with carotenoids and/or chlorophyllide in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 5 publications
3
10
0
Order By: Relevance
“…The absorption spectrum of PPIX, with peaks in the blue, green, and red spectral regions, fits the published action spectra for these herbicides (11,12,31,32). Duke and Kenyon (7) argued that the toxic oxygen species in NDPE action is singlet oxygen and Haworth and Hess (15) recently demonstrated that singlet oxygen is the active toxic oxygen species in NDPE action. After dark incubation with the herbicide, the temperature independence of the light-induced photodestruction indicates that a photodynamic dye is responsible for the activity (17).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The absorption spectrum of PPIX, with peaks in the blue, green, and red spectral regions, fits the published action spectra for these herbicides (11,12,31,32). Duke and Kenyon (7) argued that the toxic oxygen species in NDPE action is singlet oxygen and Haworth and Hess (15) recently demonstrated that singlet oxygen is the active toxic oxygen species in NDPE action. After dark incubation with the herbicide, the temperature independence of the light-induced photodestruction indicates that a photodynamic dye is responsible for the activity (17).…”
supporting
confidence: 66%
“…We previously speculated that yellow tissues are more sensitive to photobleaching herbicides than are green tissues because they lack the photosynthetic reducing capacity to generate protectants (6,7). To support this hypothesis, we have shown that a smaller concentration of PPIX in the tissue is correlated with a particular herbicidal effect in yellow (tentoxin-treated) than in green tissues (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…In the presence of light and molecular oxygen, singlet oxygen is generated and membrane lipids undergo lipid peroxidation chain reactions, resulting in rapid cellular disruption. This scheme is entirely consistent with all available data, including the rapid appearance of Proto IX (11,13), the apparent appearance of porphyrins in the plasma membrane (5,24), and the rapid loss of plasma membane integrity (15,62,63) in treated cells.…”
Section: The Unique Mechanism Of Protox Inhibitorssupporting
confidence: 89%
“…In 1989, chlorimuron, a sulfonylurea, and ima zaquin, an imidazolinone, were applied to over 50% of the soybean acreage in Mississippi for POST broadleaf weed control 4 . These herbicides inhibit acetolactate synthase (ALS) 5 , also known as acetohydroxyacid syn-thase, the first common enzyme in the biosynthetic pathway of the branched chain amino acids valine, leucine, and isoleucine (1,2,8). The systemic action of these herbicides inhibits growth and causes eventual death of susceptible weeds such as common cocklebur, pigweeds (Amaranthus spp.…”
Section: Introductionmentioning
confidence: 99%